Younger semi‐captive Asian elephants constitute suitable repository for conservation translocation - Hnin Nandar; Li‐Li Li; Zaw Min Oo; Ye Htet Lwin; Rui‐Chang Quan (Conservation Science and Practice)
Abstract Interdisciplinary efforts are fundamental for achieving successful conservation translocations. However, behavioral information is usually lacking to guide conservation translocations for social animals. This is particularly significant for the conservation of endangered Asian elephants. Therefore, by tracing the long‐term behavioral logbook records in the southern central part of Myanmar, our study highlighted that younger semi‐captive elephants (male ≤21 years old; female ≤42 years old) were identified as suitable candidates for translocations since they were more easily accepted by the wild population, with fewer fighting events and higher mingling probability. Furthermore, we recorded 136 present data combining field surveys and collection from literature, and we identified 4349.69 km2 of suitable habitat in this region located around 10 km away from the villages, closer to managed forests and water. This study integrated ecological and behavioral information to support reinforcement conservation for Asian elephants in Southeast Asia, where most of the semi‐captive elephants are distributed. These insights could guide more effective reinforcement projects by considering age and sex for improved success in integration. Additionally, our study emphasizes the importance of habitats near human‐dominated areas, which are preferred by elephants, offering practical implications for habitat management and human‐elephant conflict mitigation efforts. Further research efforts from the behavioral perspectives, such as using camera trappings or video recordings, are encouraged to facilitate social animal conservation.